2020
DOI: 10.1111/jfr3.12625
|View full text |Cite
|
Sign up to set email alerts
|

Design of low impact development in the urban context considering hydrological performance and life‐cycle cost

Abstract: The pressures on water system are increasing in cities. Rapid urbanisation caused by booming population leads to more impervious area and less infiltration, with the consequence of larger runoff volume and higher flood risk. Launched in 2014, the low impact development (LID), an important part of Sponge City in China initiative, invests in projects that aim to restore the water cycle in the urban area. A comprehensive understanding of the performance of LID measures at watershed scale under different rainfall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 52 publications
(66 reference statements)
0
33
0
Order By: Relevance
“…Several studies have confirmed that LIDs (Sustainable Drainage Systems, SUDs) have a positive impact on the hydrological and hydraulic load of traditional urban drainage systems; however, the biggest reduction was achieved in cases of small, relatively frequent rainfall events and more pervious soil types [199][200][201][202][203][204]. In case of extreme rainfall events, such a reduction in flow (water volume) is very limited and sensitive to local conditions.…”
Section: Rainfall-runoff Models and The Decision-making Processmentioning
confidence: 99%
“…Several studies have confirmed that LIDs (Sustainable Drainage Systems, SUDs) have a positive impact on the hydrological and hydraulic load of traditional urban drainage systems; however, the biggest reduction was achieved in cases of small, relatively frequent rainfall events and more pervious soil types [199][200][201][202][203][204]. In case of extreme rainfall events, such a reduction in flow (water volume) is very limited and sensitive to local conditions.…”
Section: Rainfall-runoff Models and The Decision-making Processmentioning
confidence: 99%
“…This is typical for auto-calibration of SCMs, where an objective function has to be defined [25]. Otherwise, the performance of SCMs is usually evaluated only with hydrological parameters (e.g., peak flow reduction, total volume) after their predetermined design and model simulation [4,16,19]. The hydrograph-based SCM design can be extremely helpful in situations where not only the peak flow is a limitation, but also the flow distribution (i.e., downstream convergence of outflows from catchments with different dynamics).…”
Section: Stormwater Control Measuresmentioning
confidence: 99%
“…In this context, the open-source Stormwater Management Model (SWMM) [15] is one of the most widely used models [16][17][18][19] enabling RR and hydraulic modeling of urban drainage. It also contains several SCM elements that can be integrated within the model, after being designed by the user separately.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most applied methodologies is the Life Cycle Assessment (LCA) and its variants of cost, Life Cycle Cost Assessment (LCCA), and energy, Life Cycle Energy Assessment (LCEA). Some studies have evaluated the LCA [37][38][39][40], energy-related analysis [39,41] and LCCA [39,40,42,43] of concrete or asphalt permeable pavement systems or coatings. Antunes et al [44], for example, conducted a systematic review of the LCA of permeable pavements, whose conclusions corroborate the need for maturation of the technique.…”
Section: Introductionmentioning
confidence: 99%